Factors Influencing Provision of Antibiotics without a Prescription at Pharmacies in Inner City of Hanoi, Vietnam 2024 - Trang, Tran Thị Thu (Journal of Health Science and Medical Therapy, 2025)
The sale of antibiotics without a prescription is a serious issue in Vietnam, particularly in the inner city of Hanoi, where this practice remains prevalent despite strict regulations. This has significant negative impacts on public health, including the issue of antimicrobial resistance. This study aims to evaluate the factors influencing the sale of antibiotics without a prescription at retail pharmacies in the inner city of Hanoi, focusing on the districts of Bac Tu Liem and Nam Tu Liem. A cross-sectional study was conducted from July to December 2024, targeting pharmacy staff at pharmacies meeting GPP (Good Pharmacy Practice) standards. Data were collected through questionnaires and analyzed using exploratory factor analysis (EFA) and linear regression. Three main factors influencing the sale of antibiotics without a prescription were identified: (1) Belief in benefits (β = 0.273), (2) Ability to perform and control behavior (β = 0.480), and (3) External influencing factors (β = 0.473). The regression model explained 52.9% of the variance in the willingness to sell antibiotics without a prescription. The findings suggest the need to strengthen training and raise awareness among pharmacy staff about the harms of selling antibiotics without a prescription while also improving policies for controlling and monitoring the sale of antibiotics to reduce this issue.